2018
DOI: 10.1111/dom.13584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of canagliflozin treatment on hepatic triglyceride content and glucose metabolism in patients with type 2 diabetes

Abstract: Aim: To evaluate the impact of the sodium glucose co-transporter 2 inhibitor canagliflozin on intrahepatic triglyceride (IHTG) accumulation and its relationship to changes in body weight and glucose metabolism. Materials and methods:In this double-blind, parallel-group, placebo-controlled, 24-week trial subjects with inadequately controlled type 2 diabetes mellitus (T2DM; HbA1c = 7.7% AE 0.7%) from two centres were randomly assigned (1:1) to canagliflozin 300 mg or placebo. We measured IHTG by proton-magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
4
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 42 publications
8
91
4
6
Order By: Relevance
“…Consistent with its lack of effect on body weight, most studies have not observed a reduction of IHTG with sitagliptin (Table ). This was particularly true for all three placebo‐controlled trials, where the average decrease of IHTG in the placebo arms (~10%‐20%) was similar to the relative decrease observed with sitagliptin by Yan et al This reduction is also in agreement with the relative ~10%‐20% reduction of IHTG observed in placebo arms of other controlled trials in patients with steatohepatitis (NASH) . Relative short duration of diabetes (~4 years) may have also promoted a better response than in previous studies, although the absolute reduction in MRI‐measured liver‐fat content was relatively small (mean reduction of ~4%) and none reached resolution of HS.…”
Section: Effect Of Sitagliptin In Nafldsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with its lack of effect on body weight, most studies have not observed a reduction of IHTG with sitagliptin (Table ). This was particularly true for all three placebo‐controlled trials, where the average decrease of IHTG in the placebo arms (~10%‐20%) was similar to the relative decrease observed with sitagliptin by Yan et al This reduction is also in agreement with the relative ~10%‐20% reduction of IHTG observed in placebo arms of other controlled trials in patients with steatohepatitis (NASH) . Relative short duration of diabetes (~4 years) may have also promoted a better response than in previous studies, although the absolute reduction in MRI‐measured liver‐fat content was relatively small (mean reduction of ~4%) and none reached resolution of HS.…”
Section: Effect Of Sitagliptin In Nafldsupporting
confidence: 84%
“…Promising results have been observed for the treatment of NAFLD in animal models and in open‐label clinical trials . Recently, a placebo‐controlled RCT in patients with T2DM reported that canagliflozin promoted weight loss and improved hepatic insulin sensitivity and insulin secretion . In those with NAFLD, cangliflozin decreased intrahepatic triglycerides (IHTG) versus baseline, but this was of borderline significance when compared to placebo (−38% vs. −20%; P = 0.09).…”
Section: Effect Of Sitagliptin In Nafldmentioning
confidence: 99%
“…However, their impact on liver histology remains to be established. Table summarizes several recent RCTs in NAFLD . Taken together, this class has been remarkably consistent in causing a 2% to 3% decrease in total body weight (1.5‐3.0 kg) and in lowering plasma aminotransferases with a placebo‐corrected reduction in intrahepatic triglyceride content of 10%‐30%.…”
Section: The Future Of Treating Nash In Patients With T2dmmentioning
confidence: 83%
“…Table 2 summarizes several recent RCTs in NAFLD. [43][44][45][46][47] Taken together, this class has been remarkably consistent in causing a 2% to 3% decrease in total body weight (1.5-3.0 kg) and in lowering plasma aminotransferases with a placebo-corrected reduction in intrahepatic triglyceride content of 10%-30%. However, decreases in intrahepatic triglyceride content must be interpreted with caution because changes in liver fat on imaging may or may not reliably correlate with necroinflammation or fibrosis on histology.…”
Section: Is There a Future Role For Sglt2i For The Treatment Of Nash?mentioning
confidence: 84%
See 1 more Smart Citation